Synthesis, optimization, characterization, and potential agricultural application of polymer hydrogel composites based on cotton microfiber - Laftah, Waham Ashaier (Walter De Gruyter, 2014)
The optimum content of cotton microfiber, initiator, cross-linker, and sodium hydroxide were determined using the central composite design method. Polymer hydrogels (PHGs) were characterized using Fourier-transform infrared (FT-IR), scanning electron microscopy, and thermal gravimetric analysis. A comparison between plain PHG and the polymer hydrogel composite (PHGC) in terms of biodegradation, swelling rate, and re-swelling capacity was carried out. The effect of PHGC on the sandy soil holding capacity, urea leaching loss rate (ULLR), and okra plant growth were evaluated. The highest water absorption capacity was obtained at 1.30 mass %, 0.15 mass %, 13.00 mass %, and 13.50 mass % of the initiator, cross-linker, sodium hydroxide, and cotton microfiber, respectively. Cotton microfiber has a prominent effect on the swelling rate, re-swelling capacity, and biodegradability of PHG. Okra plant growth and ULLR were positively affected by PHGC and the best leaching loss rate of 33.3 mass % was observed for the lowest urea loaded sample.